Coadministration of lorcaserin and phentermine for weight management: A 12‐week, randomized, pilot safety study. Issue 5 (May 2017) - Smith, Steven R.; Garvey, W. Timothy; Greenway, Frank L.; Zhou, Sharon; Fain, Randi; Pilson, Robert; Fujioka, Ken; Aronne, Louis J.
Abstract : Objective: To assess the short‐term tolerability of lorcaserin alone or with two dose regimens of phentermine. Methods: This was a 12‐week, randomized, double‐blind, pilot safety study of N  = 238 nondiabetic patients with obesity or overweight with ≥1 comorbidity randomized to lorcaserin 10 mg twice daily (BID; LOR BID) alone or with phentermine 15 mg once daily (QD; LOR BID+PHEN QD) or 15 mg twice daily (LOR BID+PHEN BID). Patients reporting ≥ 1 of 9 potentially serotonergic adverse events (AEs), mean weight loss (WL), and ≥5% WL are reported. Results: N  = 238 were randomized, and N  = 235 were treated. N  = 94 reported potentially serotonergic AEs: 37.2% LOR BID, 42.3% LOR BID+PHEN QD, and 40.5% LOR BID+PHEN BID. AEs leading to discontinuation were reported approximately twice as often in the LOR BID+PHEN BID group versus the LOR BID group. Mean WL was 3.5 kg/3.3%, 7.0 kg/6.7%, and 7.6 kg/7.2% for LOR BID, LOR BID+PHEN QD, and LOR BID+PHEN BID, respectively. At least 5% WL was achieved by 28.2% LOR BID, 59.0% LOR BID+PHEN QD ( P  = 0.0002 vs. LOR BID), and 70.9% LOR BID+PHEN BID ( P  < 0.0001 vs. LOR BID) patients. Conclusions: Phentermine added to lorcaserin enhanced short‐term weight loss but did not increase incidence of potentially serotonergic AEs; however, phentermine twice daily increased discontinuation compared to both lorcaserin alone and lorcaserin plus phentermine once daily.